Conditional Volatility in Foreign Exchange Rates: Evidence from the Malaysian Ringgit and Singapore Dollar - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1997)
In this paper we examine the conditional volatility of the exchange rates of two Asia-Pacific currencies. These are the Malaysian ringgit-US dollar and the Singapore dollar-US dollar exchange rates. Both currencies are under relatively intervention-free managed-float systems. We employ the new class of APARCH model of Ding et al. (1993) to capture the possibly asymmetric effects of exchange shocks on future volatilities. In addition, we take account of the nonnormality in the residuals by using f-distributed errors. Similar to the findings for the major currencies under flexible exchange rate systems, the exchange rates of the two Asia-Pacific currencies demonstrate conditional heteroscedasticity and are adequately described by the APARCH model. We also find that a depreciation shock in the Malaysian ringgit against the US dollar has a greater effect on future volatilities than an appreciation shock of the same magnitude. However, such asymmetric effects are not significant in the Singapore market.